2013
DOI: 10.1371/journal.pone.0064857
|View full text |Cite
|
Sign up to set email alerts
|

Higher Isolation of NDM-1 Producing Acinetobacter baumannii from the Sewage of the Hospitals in Beijing

Abstract: Multidrug resistant microbes present in the environment are a potential public health risk. In this study, we investigate the presence of New Delhi metallo-β-lactamase 1 (NDM-1) producing bacteria in the 99 water samples in Beijing City, including river water, treated drinking water, raw water samples from the pools and sewage from 4 comprehensive hospitals. For the bla NDM-1 positive isolate, antimicrobial susceptibility testing was further analyzed, and Pulsed Field Gel Electrophoresis (PFGE) was performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 12 publications
(16 reference statements)
1
64
1
Order By: Relevance
“…In China, bla NDM-1 gene could be detected in different bacteria species, such as Acinetobacter baumannii, Enterobacter cloacae, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa [14][15][16][17]. However, carbapenem-resistant A. soli isolate carried bla NDM-1 gene has been detected in our study, which indicated that it could disseminate more widely and promptly than we anticipated, and its prevalence should be monitored with care.…”
contrasting
confidence: 51%
“…In China, bla NDM-1 gene could be detected in different bacteria species, such as Acinetobacter baumannii, Enterobacter cloacae, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa [14][15][16][17]. However, carbapenem-resistant A. soli isolate carried bla NDM-1 gene has been detected in our study, which indicated that it could disseminate more widely and promptly than we anticipated, and its prevalence should be monitored with care.…”
contrasting
confidence: 51%
“…Majority of the Acinetobacter baumannii isolates belong to ST25, where ST is an emergent clonal lineage which includes Carbapenemases including oxacillinases (OXA-58 and OXA-72), metallo-ß-lactamases (NDM-1) and recently for the first time OXA-23 mediated Carbapenem resistance in sequence type 2 multidrug-resistant Acinetobacter baumannii was recorded from a cat with urinary tract infection. A recent study demonstrated increased resistance of A. baumannii towards dessication and its biofilm forming ability on abiotic surfaces which facilitates its persistence in hospital environment , one more study revealed the isolation of carbapenem-resistant A. baumannii from hospital sewges in Beijing (Zhang et al, 2013). A multicentre cross-sectional study conducted to detect the carriage of Acinetobacter baumannii in pets revealed a carriage prevalence of…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…Published papers on CRBP in nature are mostly focused on single bacterial isolates. Viable isolates of CRBP were recovered from hospital sewage both before and after disinfection (Ferreira et al, 2011;Chagas et al, 2011;Zhang et al, 2013;Chandran et al, 2014). From the mixture of domestic and hospital wastewaters two carbapenem-resistant Klebsiella pneumoniae and one Escherichia coli were recovered (Galler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…From the mixture of domestic and hospital wastewaters two carbapenem-resistant Klebsiella pneumoniae and one Escherichia coli were recovered (Galler et al, 2014). From municipal sewage in Beijing, 37 isolates of CRBP were isolated (Zhang et al, 2013). Carbapenem-resistant isolates of A. baumannii were recovered from raw and secondary treated municipal wastewater (Hrenovic et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation